TELAAH UNSUR BATIN DALAM PUISI BERJUDUL SAJAK IBU KARYA WIJI THUKUL - Pratama, Yosi; Sobari, Teti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
A written work created by someone, is not just a form of expression in expressing his ideas or ideas. But there is a mission or other purpose that he wants to convey to all readers. This study aims to determine the inner elements of poetry in terms of theme, taste, tone and message. The method that the author uses is descriptive qualitative with text as the source of data and the object of the research. Of the many literary works of poetry produced by Indonesian writers, there is one interesting title of poetry to be studied, namely the poem "rhyme mother" by the poet whose writing is free and active. namely Wiji Thukul. The results of this study indicate that the poem has the theme of humanity, which contains feelings of longing and deep wounds. While the implied feelings are none other than feelings of grief. The tone and atmosphere of the poem are light and easy to understand by the readers. So that the reader seems to be carried away with the events in it. In addition, the mandate in this literary work of poetry is a call to glorify or appreciate someone who is present in everyone's life. The work reveals the position or self-esteem of a noble human being. Of course, family is the most expensive asset that is difficult to replace with objects or other things.